2022
DOI: 10.18805/ijar.b-4747
|View full text |Cite
|
Sign up to set email alerts
|

​Localization of Orexin and its Receptor in Corpus Luteum and in vitro Effect of Orexin on Progesterone Production from Luteal Cells in Buffalo

Abstract: Background: Orexin is a hypothalamic neuropeptide involved in regulating various biological functions, including reproduction. The study aimed to investigate the immunolocalization of orexin and its receptors in the corpus luteum in buffalo (Bubalus bubalis) ovary and the effect of orexin on progesterone production. Methods: The study was carried out on buffalo ovaries, each with a different developmental stage of corpus luteum (CL) (n=10 for each stage). The CLs were separated out from ovaries for immunolocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In our previous studies, we have demonstrated the expression of the PPO and orexin receptors (OX1R and OX2R) in the corpus luteum of the buffalo ovary (Sardar et al, 2020). We also observed the physiological role of OXA on progesterone production from luteal cells (Sardar et al, 2023).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In our previous studies, we have demonstrated the expression of the PPO and orexin receptors (OX1R and OX2R) in the corpus luteum of the buffalo ovary (Sardar et al, 2020). We also observed the physiological role of OXA on progesterone production from luteal cells (Sardar et al, 2023).…”
Section: Discussionmentioning
confidence: 62%
“…All these shreds of evidence specifically suggest the local presence of the orexigenic system on ovarian follicles. Not only in the follicles, but the presence of orexins and their receptors have also been reported in corpus luteum in the ovary of rats (Cataldi et al, 2012), pigs (Basini et al, 2018;Nitkiewicz et al, 2014) and buffalo (Sardar et al, 2020(Sardar et al, , 2023. Apart from the ovary, the presence of the orexigenic system has been documented in other female and male reproductive tissues, including the placenta and uterus (Smolinska et al, 2015) and testes (Barreiro et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation